Financial toxicity of childhood cancer and changes to parents' employment after treatment completion. Issue 7 (25th April 2020) - Kelada, Lauren; Wakefield, Claire E.; Vetsch, Janine; Schofield, Deborah; Sansom‐Daly, Ursula M.; Hetherington, Kate; O'Brien, Tracey; Cohn, Richard J.; Anazodo, Antoinette; Viney, Rosalie; Zeppel, Melanie J.B.
Abstract: Objective: Childhood cancer can have short‐ and long‐term impacts on parents' finances and employment. It is important to understand how families adjust to the financial and employment changes caused by childhood cancer, the ongoing impacts after treatment completion, and which families need more targeted support. Qualitative research is necessary to facilitate an in‐depth understanding of the employment and financial impacts on families and to capture parents' complex and nuanced experiences and perspectives. Methods: We interviewed 56 parents of childhood cancer survivors ( M = 2.13 years after treatment completion; 89% mothers) using the vocational and financial impact section of the Psychosocial Adjustment to Illness Scale–Carer Interview Form. We analyzed interviews using content analysis. Results: Parents reported multiple sources of financial toxicity including travel to and from the hospital and needing to reduce their working hours during their child's cancer treatment. Workplace flexibility was an important factor to protect against unwanted vocational changes. After treatment completion, families living in low socioeconomic areas commonly reported ongoing financial difficulties. Mothers, particularly those who were on maternity leave when their child was diagnosed with cancer, reported ongoing employment impacts including unemployment. Conclusions: Clinical staff including social workers could more consistently assess families' financial distress and refer to professional services who can offer guidance for financial decision‐making as standard care. Flexible workplace agreements appear important for parents of children with cancer. Our findings can assist organizations to understand that cancer‐related disruptions are likely to continue after treatment completion, and therefore should offer benefits to parents where possible.